THE ROLE OF DIAGNOSTIC TECHNOLOGIES AND CLINICAL BIOMARKERS IN THE MANAGEMENT OF DIABETIC RETINOPATHY (CIPEEX, 2025)
Introduction: in patients with diabetes mellitus, diabetic retinopathy (DR) is a common microvascular complication that, if not diagnosed early, can lead to blindness. Early diagnosis and prevention of DR are crucial. Emerging technologies such as artificial intelligence (AI) and glucose monitoring offer new approaches for screening and managing this condition. Objective: to consolidate the findings of recent research on the clinical characteristics and technological approaches that influence the diagnosis and progression of DR. Methodology: classified as a simple literature summary based on three articles found in the PubMed (Public Medline) database. The health descriptors "Diabetes Mellitus", "Diabetic Retinopathy", "Clinical Diagnosis" and "Technology" were used, in addition to the boolean operator "AND" between them. Articles published between 2020 and 2025 that met the objective of the present summary were selected. Results: it was verified that in patients with type 2 diabetes and diabetic kidney disease, the use of insulin, a longer duration of diabetes and high systolic blood pressure levels were associated with the presence of DR. In individuals with type 1 diabetes, remnant cholesterol was associated with hyperglycemia and diabetic nephropathy, but not with DR. It was also observed that the retinal age gap was significantly greater in patients with DR than in those without DR. These results suggest that premature aging of the retina is associated with disease progression. Conclusion: the use of technologies such as AI for the screening and diagnosis of DR is promising, given that the retinal age gap can serve as a predictive biomarker for disease progression. Furthermore, clinical risk factors, such as insulin use, duration of diabetes and high systolic blood pressure, continue to be important predictors of DR in patients with type 2 diabetes. Future research should continue to explore the integration of biomarkers and technologies to optimize the screening and management of diabetic retinopathy.
Keywords: diabetic retinopathy; diabetes mellitus; technology; Clinical diagnosis